d-tyrosine enhances disoctyl dimethyl ammonium chloride on alleviating SRB corrosion - Jingyi Zhou; Hongyi Li; Shichu Gong; Shuguang Wang; Xianzheng Yuan; Chao Song (Heliyon, 2023)
Microbiologically influenced corrosion (MIC) caused by sulfate reducing bacteria (SRB) is a serious challenge in many industries, but biofilm greatly decreases the toxicity of bactericides to cell inside. d-amino acids are potential enhancers for bactericides due to their excellent performance on biofilm inhibition. However, the mechanism of d-amino acid cooperating with bactericides for MIC inhibition is still unknown. In this study, d-tyrosine（D-Tyr）and disoctyl dimethyl ammonium chloride (DDAC) were selected as the typical d-amino acid and bactericide, respectively, to evaluate their synergetic inhibition on the corrosion caused by Desulfovibrio vulgaris. D-Tyr obviously enhanced the role of DDAC in inhibiting corrosion with high corrosion inhibition efficiency at 77.23 %. The attachment of EPS and live cells on the coupon surface decreased in the presence of D-Try, leading to more cells directly exposed to DDAC. Besides, D-Try decreased the amount of live cells on the surface and thus reduced the utilization of Fe by SRB and corrosion current. Moreover, dead cells settling to the coupon surface may form a protective lay to retard the contact between live SRB and Fe, leading to slow cathode reaction and less corrosion. Therefore, D-Tyr can reduce the coverage of biofilm, thereby reducing its protective effect on SRB and achieving better corrosion inhibition effect. This work provides a new strategy for improving bactericides and inhibiting MIC.